1996
DOI: 10.1152/ajpregu.1996.271.4.r1070
|View full text |Cite
|
Sign up to set email alerts
|

Processing of vestibular and other inputs by the caudal ventrolateral medullary reticular formation

Abstract: Lesions of the lateral medullary reticular formation caudal to the obex abolish vestibulosympathetic and somatosympathetic responses; this area also contains neurons that mediate baroreceptor reflexes. Recordings were made from neurons in the caudal medullary reticular formation of cats that were decerebrate or anesthetized using alpha-chloralose-urethan to determine whether common neurons responded to electrical stimulation of vestibular and hindlimb afferents and had cardiac-related (i.e., baroreceptor) inpu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 0 publications
0
25
0
Order By: Relevance
“…Eight neurons responded to both cardiovascular and gastrointestinal stimulation and were classified as convergent neurons. Although transient changes in blood pressure often occurred after delivery of copper sulfate (52,53), the sustained changes in firing rate elicited by infusion of the compound were not synchronized with these blood pressure perturbations. The 31 cells with cardiac-related activity or responses to carotid stretch that were not deemed to be convergent units were classified as cardiovascular neurons.…”
Section: Resultsmentioning
confidence: 95%
“…Eight neurons responded to both cardiovascular and gastrointestinal stimulation and were classified as convergent neurons. Although transient changes in blood pressure often occurred after delivery of copper sulfate (52,53), the sustained changes in firing rate elicited by infusion of the compound were not synchronized with these blood pressure perturbations. The 31 cells with cardiac-related activity or responses to carotid stretch that were not deemed to be convergent units were classified as cardiovascular neurons.…”
Section: Resultsmentioning
confidence: 95%
“…The vestibular nuclei provide direct inputs to the RVLM (28,35), as well as indirect inputs relayed through brain stem regions that mediate the baroreceptor reflex and participate in generating rhythmic SNA, including nucleus tractus solitarius (1,37,41), the lateral tegmental field (40), and the caudal ventrolateral medulla (38). One explanation for the reduced RVLM neuronal activity after the elimination of labyrinthine inputs is a loss of excitatory monosynaptic and polysynaptic excitatory drive to RVLM neurons from the vestibular nuclei.…”
Section: Discussionmentioning
confidence: 99%
“…Although the level at which this interaction occurs is unclear, it is generally accepted that the VSR and baroreflexes share common neural pathways (2,45,(51)(52)(53)55). An orthostatic challenge or stimulation of vestibular nuclei is known to cause increases in muscle or renal sympathetic nerve activity (10,36,38,54), and in the presence of intact baroreflexes these responses are augmented (37,38,40).…”
Section: Discussionmentioning
confidence: 99%
“…Impairment of the baroreflex would produce inadequate homeostatic responses to the changing posture that lead to orthostatic hypotension (6, 15, 25). Therefore, neural interaction between VSR and baroreflexes are important in understanding the hemodynamic changes that occur during postural changes.Previous neuroanatomical and electrophysiological studies have shown direct projections from vestibular nuclei to brain stem nuclei regulating cardiovascular functions including nucleus tractus solitarius (NTS), dorsal motor vagal nucleus, nucleus ambiguous, caudal ventrolateral medulla (CVLM), and rostral ventrolateral medulla (RVLM) (2,45,(51)(52)(53)55). Direct stimulation of the vestibular nerves in animals results in increased sympathetic activity to a number of vascular beds (5,23,32,54).…”
mentioning
confidence: 99%